O problema dinâmico de re-configuração de linhas de montagem - Ormeu Coelho da Silva Junior (2007)
This work investigates a version of the assembly line balancing problem in witch the variations on demand levels makes its re-configuration desirable. It reflects aspects related with changing the structure and the operation patterns of the assembly lines. We consider the costs due to tasks reallocation, station activation and a wage tax ateach active station. We also consider the occurrence of a profit each time a station is closed. Simultaneously the station workload is forced to fall into a predefined interval. Four integer programming formulations are proposed to the variations of the problem and three of them do the re-configuration under a discrete time horizon with dynamic demands. The computational performance of the models are improved through theadaptation of lower bounds available for the Simple Assembly Line Balancing Problem (SALBP) and two reduction rules were developed for the problem versions based on smoothening restrictions. Computational experiments for the four formulations are reported. It covers tests with instances adapted from literature and random generated examples. Three real cases of mono-product assembly lines reconfiguration at an electronic industry were analyzed and the proposed approach compared to classical literature methods and to the enterprise practices. The results show our approach is successful in reducing the total costs with re-configuration and operation of flexible assembly systems through managing its capacity.